2020
DOI: 10.1088/1742-6596/1431/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature fields and bottom sediments of oil products on the stress-strain state of the design of a vertical steel tank

Abstract: Tanks for storing oil and oil products during operation are exposed to a combination of external, static, low-cycle, temperature, snow and wind loads, bottom sediments, etc., which leads to a decrease in operational reliability and a decrease in the durability of tank structures. Numerical modeling methods, in contrast to standard methods for calculating strength and stability, allow us to create an adequate finite element model at the stage of development of a geometric model. This article describes the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…When storing petroleum products, soil contamination occurs due to frequent leaks from reservoirs or non-compliance with pumping processes (Lee et al 2019 ; Gorawski et al 2017 ; Sacile 2007 ). When storing viscous petrochemicals, sediments can accumulate due to incompatibility of petroleum products, which can affect the corrosion of the metal, the stress–strain state of the reservoir structure, and accident rate resulting in the ingress of petroleum products into the soil (Sultanbekov et al, 2019a , 2019b , 2020 ). It is found that industrial facilities such as gas stations, despite the relatively small taken area, contribute significantly to the contamination of adjacent soils with petroleum products that also occurs due to leaks from fuel storage tanks (Aulia et al 2016 ; Iurchenko et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…When storing petroleum products, soil contamination occurs due to frequent leaks from reservoirs or non-compliance with pumping processes (Lee et al 2019 ; Gorawski et al 2017 ; Sacile 2007 ). When storing viscous petrochemicals, sediments can accumulate due to incompatibility of petroleum products, which can affect the corrosion of the metal, the stress–strain state of the reservoir structure, and accident rate resulting in the ingress of petroleum products into the soil (Sultanbekov et al, 2019a , 2019b , 2020 ). It is found that industrial facilities such as gas stations, despite the relatively small taken area, contribute significantly to the contamination of adjacent soils with petroleum products that also occurs due to leaks from fuel storage tanks (Aulia et al 2016 ; Iurchenko et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, asphaltenes of thermo-destructive processes have lower aggregative stability in the colloidal system than asphaltenes of natural origin. Since asphaltenes of secondary origin formed during thermolysis have a less complex composition and molecular structure and less branching, they have lower solubility compared to natural asphaltenes [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the processing of crude oil raw materials will be relevant. The chemical composition of middle distillate oil fractions is their most important parameter, influencing the methods for further processing, storage, and transportation. The components of delayed coking distillate products consist of different classes of hydrocarbon compounds: alkanes, cycloalkanes, alkenes, aromatic hydrocarbons, and various heterocyclic compounds containing oxygen, sulfur, and nitrogen. The hydrocarbon group composition depends on the oil fraction origin.…”
Section: Introductionmentioning
confidence: 99%